2017
DOI: 10.1093/toxsci/kfx267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclophosphamide and/or Doxorubicin in a Murine Model of Postchemotherapy Cognitive Impairment

Abstract: Postchemotherapy cognitive impairment, or PCCI, is a common complaint, particularly among breast cancer patients. However, the exact nature of PCCI appears complex. To model the human condition, ovariectomized C57BL/6J mice were treated intravenous weekly for 4 weeks with saline, 2 mg/kg doxorubicin (DOX), 50 mg/kg cyclophosphamide (CYP), or DOX + CYP. For the subsequent 10 weeks, mice were assessed on several behavioral tests, including those measuring spatial learning and memory. After sacrifice, hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 84 publications
7
14
1
Order By: Relevance
“…The results from this study indicated that the administration of CYP induced motor and behavioral defects as illustrated by the rotarod and open field tests. Previous studies showed that chemotherapy alters locomotive activity and motor coordination [31] . This result obtained from this study indicated that CYP drastically impaired muscle grip, motor coordination and locomotive activity.…”
Section: Discussionsupporting
confidence: 74%
“…The results from this study indicated that the administration of CYP induced motor and behavioral defects as illustrated by the rotarod and open field tests. Previous studies showed that chemotherapy alters locomotive activity and motor coordination [31] . This result obtained from this study indicated that CYP drastically impaired muscle grip, motor coordination and locomotive activity.…”
Section: Discussionsupporting
confidence: 74%
“…Multiple studies have demonstrated that chemotherapeutic agents impair performance in behavioral tasks mediated by the Hcc (Christie et al, 2012; Kitamura et al, 2015; Lyons et al, 2011; Macleod et al, 2007; Mustafa et al, 2008; Yang et al, 2010). The present finding that repeated DOX+CYP administration impairs Hcc-mediated spatial memory is in agreement with studies conducted in male Wistar rats (Kitamura et al, 2015, 2017) but is at odds with another study examining DOX+CYP-induced cognitive impairment in female C57Bl/6J mice (Flanigan et al, 2018). However, this latter study used ovariectomized mice in order to prevent alterations in cognitive function caused by changes in circulating estrogen, whereas our study and the studies of Kitamura et al (2015, 2017) used animals with intact gonads.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other reports (Flanigan et al, 2018), the repeated administration of DOX+CYP to mice resulted in a ≈5%–10% reduction in weight that was not observed in saline-injected mice. The weight of mice on standard diet returned to baseline 2 weeks after the final administration of DOX+CYP, but the weight of mice on 2% Ch diet remained low for the remainder of the study.…”
Section: Discussionsupporting
confidence: 90%
“…1A for study time line). The dosages selected were based on our preliminary work and other previous studies [ 25 26 ], which showed that animals tolerated these doses with minimal weight loss and death ( Fig. 1B ).…”
Section: Methodsmentioning
confidence: 99%